2015
DOI: 10.1093/scan/nsv090
|View full text |Cite
|
Sign up to set email alerts
|

The validity of individual frontal alpha asymmetry EEG neurofeedback

Abstract: Frontal asymmetry in alpha oscillations is assumed to be associated with psychopathology and individual differences in emotional responding. Brain-activity-based feedback is a promising tool for the modulation of cortical activity. Here, we validated a neurofeedback protocol designed to change relative frontal asymmetry based on individual alpha peak frequencies, including real-time average referencing and eye-correction. Participants (N = 60) were randomly assigned to a right, left or placebo neurofeedback gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 71 publications
4
65
0
1
Order By: Relevance
“…Figure 2C shows that as hypothesized, following amyg-EFP NF only the EFP-Test group showed reduced reactivity of the amygdala relative to before training (EFP- Test: F(1,11 groups (F(1,11)=0.01, p>0.92). However, the ANOVA did not reveal a significant Group*Time-Point interaction (F (1,11)=1.44, p>0. 25), preventing a definite dissociation between the groups.…”
Section: Experiments 2: Neural Effects Of Amyg-efp Nfmentioning
confidence: 79%
See 1 more Smart Citation
“…Figure 2C shows that as hypothesized, following amyg-EFP NF only the EFP-Test group showed reduced reactivity of the amygdala relative to before training (EFP- Test: F(1,11 groups (F(1,11)=0.01, p>0.92). However, the ANOVA did not reveal a significant Group*Time-Point interaction (F (1,11)=1.44, p>0. 25), preventing a definite dissociation between the groups.…”
Section: Experiments 2: Neural Effects Of Amyg-efp Nfmentioning
confidence: 79%
“…Electroencephalography (EEG) on the other hand, is a relatively inexpensive and mobile brain imaging technique that can be easily implemented at any location. Albeit, the clinical benefit of EEG-NF, particularly for affective disturbances such as depression and post-traumatic stress disorder (PTSD), remains dubious (10,11); possibly due to poor spatial resolution, which hampers the targeting of deep limbic areas such as the amygdala (12). The current study conducted a first of its kind investigation of the neurobehavioral implications of a novel imaging approach that allows for the bed-side monitoring of amygdala activity using fMRI-inspired EEG; hereby termed, "amygdala-EEG Finger Print" (amyg-EFP).…”
Section: Introductionmentioning
confidence: 99%
“…That is, participants who received neurofeedback training to increase relative right frontal activity showed a significant increase in relative right frontal activity from Day 1 to Day 3 and 4. In contrast, individuals who received training to increase relative left frontal activity did not show a significant increase in relative left frontal activity, but they did differ significantly from those who had received relative right frontal training (for a replication, see Quaedflieg et al, ). As predicted, this manipulated change in asymmetric frontal cortical activity caused changes in affective responses.…”
Section: The Relationship Of Asymmetric Frontal Cortical Activity Witmentioning
confidence: 99%
“…For example, Baehr and colleagues used an alpha asymmetry protocol in two different sets of case studies to successfully treat depression in patients also being treated with psychotherapy (Baehr & Baehr, 1997;Baehr, Rosenfeld, Baehr, & Earnest, 1999). Quaedflieg et al (2016) showed that frontal alpha asymmetry neurofeedback can result in changes in relative frontal asymmetry at rest, suggesting it is potentially a powerful tool for use in the treatment of depression. Mennella, Patron, and Palomba (2017) extended these findings by showing that frontal alpha asymmetry neurofeedback led to significant changes in resting asymmetry as well as changes in negative mood and anxiety.…”
Section: Frontal Asymmetry Neurofeedbackmentioning
confidence: 99%